Up-regulated lncRNA LINC00858 facilitates proliferation and migration of gastric cancer cells - Qin, Lianjin; Yao, Fenfen; Yu, Hongbin; Xu, Yongqiang; Jin, Yude; Dong, Wei (Polish Journal of Pathology, 2020)
Previous evidence has shown that the long intergenic non-protein coding RNA 858 (LINC00858) is an oncogene in non-small cell lung cancers. However, the role LINC00858 plays in gastric cancer (GC) is not clear. To illustrate the role LINC00858 plays in GC, the LINC00858 expression in GC and normal tissues was firstly detected. Then, the viability, proliferation and migration of GC BGC823 and MGC803 cells were assessed following LINC00858 knockdown by si-LINC00858 transfection. The results showed that LINC00858 had a high level of expressions in GC tissues as demonstrated by both online data and qRT-PCR assay. Also, the knockdown of LINC00858 reduced the proliferation and migration of BGC823 and MGC803 cells in vitro. Taken together, our data indicate that LINC00858 plays an oncogenic role in GC cells and might act as a potential therapeutic target for GC.